Analisa Tingkat Kerusakan Dan Estimasi Biaya Perawatan Bangunan Gedung Utama Sekolah Tinggi Teknologi Indragiri - M. Gemilang; Nedra Neswita; Sri Agustin (Jurnal Sipil Terapan, 2023)
Building as an educational service requires maintenance so that the condition of the building remains fit for function. Without building maintenance activities, the function of a building will experience degradation over time. In this study, researchers focused on research on the Main Building of the Indragiri High School of Technology which was more than 10 years old to analyze the level of damage to the building and estimate the cost of maintaining the building. In the calculation that the level of damage is calculated based on the Regulation of the Minister of Public Works Number 24/PRT/M/2008 concerning Guidelines for the Maintenance and Care of Buildings, from the sum of all the components, 89.0% is categorized as Severely Damaged with the greatest damage in structural damage. The estimated maintenance cost for the main building of the Indragiri High School of Technology is Rp. 467,929,000.00 including Four Hundred Sixty Seven Nine Hundred Twenty Nine Thousand Rupiah